Breastfeeding Status and Infectious Diseases among Children Aged 6–23 Months in Indonesia - Bunga A. Paramashanti; Esti Nugraheny; Suparmi Suparmi; Tin Afifah; Wahyu Pudji Nugraheni; Sinta Dewi Lestyoningrum; Tumaji Tumaji; Ning Sulistiyowati; Siti Masitoh; Herwinda Kusuma Rahayu; Effatul Afifah (Asian Journal of Social Health and Behavior)
Introduction: Infectious diseases remain public health issues in Indonesia. However, there remains a knowledge gap on whether breastfeeding can prevent infectious diseases in young children. This study examined the relationship between current breastfeeding and child infections in Indonesia. Methods: Data were derived from the 2017 Indonesia Demographic and Health Survey by including 5158 children aged 6–23 months. The dependent variables were diarrhea, fever, and acute respiratory infection (ARI). The main exposure of interest was the current breastfeeding status. Covariates included factors at the child, maternal, household, health care, and community levels. Results: Around 20%, 38%, and 4% of children experienced diarrhea, fever, and ARI, respectively. Current breastfeeding status was protective against diarrhea (adjusted odds ratio [AOR] = 0.74, 95% confidence interval [CI] = 0.61–0.89) but not related to fever (AOR = 0.95, 95% CI = 0.82–1.11) and ARI (AOR = 1.01, 95% CI = 0.70–1.47). Other factors related to diarrhea included female children, older maternal age, maternal higher education, improved drinking water source, and living in Sulawesi. Living in Sumatera and Sulawesi were linked to fever. Higher birth orders and improved toilet facilities were associated with ARI. Conclusion: The findings indicate different levels of factors affecting child infections. Thus, integrating breastfeeding promotions with water, hygiene, and sanitation interventions may help prevent infectious diseases in young children.